Persistent Viral Presence Determines the Clinical Course of the Disease in COVID-19 - Chang, De (J Allergy Clin Immunol Pract, 2020)
BACKGROUND: The clinical management of coronavirus disease 2019 (COVID-19) is dependent on understanding the underlying factors that contribute to the disease severity. In the absence of effective antiviral therapies, other host immunomodulatory therapies such as targeting inflammatory response are currently being used without clear evidence of their effectiveness. Because inflammation is an essential component of host antiviral mechanisms, therapies targeting inflammation may adversely affect viral clearance and disease outcome. OBJECTIVE: To understand whether the persistent presence of the virus is a key determinant in the disease severity during COVID-19 and to determine whether the viral reactivation in some patients is associated with infectious viral particles. METHODS: The data for patients were available including the onset of the disease, duration of viral persistence, measurements of inflammatory markers such as IL-6 and C-reactive protein, chest imaging, disease symptoms, and their durations among others. Follow-up tests were performed to determine whether the viral negative status persists after their recovery. RESULTS: Our data show that patients with persistent viral presence (>16 days) have more severe disease outcomes including extensive lung involvement and requirement of respiratory support. Two patients who died of COVID-19 were virus-positive at the time of their death. Four patients demonstrated virus-positive status on the follow-up tests, and these patient samples were sent to viral culture facility where virus culture could not be established. CONCLUSIONS: These data suggest that viral persistence is the key determining factor of the disease severity. Therapies that may impair the viral clearance may impair the host recovery from COVID-19.